1) Rozwiąż równania:
3x+4=-2

5-4x=10

3(2x+1)=12

2x- (3x+6) = 3(x+1)

2- (4x+1) = 3-2x

2) Doprowadź wyrażenie do najprostszej postaci:
3x- (4x+1) 2- (4x-1) =

(3x-1)(x+1) + (2x+1)(x-3) =

3- (4x+1) + (3x-2)(x+5) =

(2x-3)(x+1) - (4x-1)(x+3) =

Proszę o pomoc proszę ! :(

2

Odpowiedzi

2010-01-05T17:27:58+01:00
1) Rozwiąż równania:
3x+4=-2
3x=-6 / :3
x=-2

5-4x=10
-4x=5 /:-4
x=-1,25

3(2x+1)=12
6x=9 /:6
x=1,5

2x- (3x+6) = 3(x+1)
-4x=-3 /:-4
x=0,75

2- (4x+1) = 3-2x
-2x=2 /:-2
x=-1

2) Doprowadź wyrażenie do najprostszej postaci:
3x- (4x+1) 2- (4x-1) =3x-8x-2-4x+1=-15x-1

(3x-1)(x+1) + (2x+1)(x-3) =3(x do kwadratu)+3x-x-1+2(x do kwadratu)-6x+x-3=2(x do kwadratu)-3x-2

3- (4x+1) + (3x-2)(x+5) = 3-4x-1+3(x do kwadratu)+15x-2x-10=-5+9x+3(x do kwadratu)

(2x-3)(x+1) - (4x-1)(x+3) =2(x do kwadratu)+2x-3x-3-4(x do kwadratu)-12x+x+3=-2(x do kwadratu)-12x-4

Najlepsza Odpowiedź!
2010-01-05T17:28:24+01:00
1
3x+4=-2
3x=-6
x=-2

5-4x=10
-4x=5
x=-5/4

3(2x+1)=12
6x+3=12
6x=9
x=9/6

2x-(3x+6)=3(x+1)
2x-3x-6=3x+3
-4x=9
x=-9/4

2-(4x+1)=3-2x
2-4x-1+2x=3
-2x=2
x=-1
2
3x- (4x+1) 2- (4x-1) =3x-8x-2-4x+1=-9x-1


(3x-1)(x+1) + (2x+1)(x-3) =3x²+3x-x-1+(2x²-6x+x-3)=3x²+2x-1+2x²-6x+x-3=5x²-3x-4

3- (4x+1) + (3x-2)(x+5) =3-4x-1+3x²+15x-2x-10=3x²+9x-11

(2x-3)(x+1) - (4x-1)(x+3) =2xkwadrat+2x-3x-3-(4xkwadrat+12x-x-3)=2xkwadrat-x-3-4xkwadrat-12x+x+3=-2xkwadrat-12x